Interpreting the Qur’an: Non-Muslim as Mufassir - Johns, Anthony H. (Islamic Studies Review, 2025)
This essay presents a reflective intellectual history of the author’s engagement with Islamic studies, specifically the challenges and insights inherent in a non-Muslim attempting to interpret (tafsīr) the Qur’an. Drawing upon decades of scholarship at the Australian National University and fieldwork in Cairo and Indonesia, Johns articulates the hermeneutical difficulty of accessing the “tone and colouring” of the Islamic revelation from outside the faith community. The narrative traces the author’s methodological turn to a literary and phenomenological appreciation of the Qur’an as a recited, oral text. Key turning points in this hermeneutical journey include the realization of the distinct nature of Islamic “salvation history”—contrasted with Biblical narratives, particularly through the story of Joseph (Yūsuf)—and the discovery of the internal coherence of the Qur’an. The essay emphasizes that understanding the Qur’an requires moving beyond textual translation to experiencing its recited reality and accepting its prophetic narratives on their own terms, independent of Judeo-Christian antecedents. Ultimately, the work argues for an empathetic scholarship that bridges the “familiar” (shared prophetic figures) and the “remote” (distinctive Islamic theology) to foster inter-religious understanding.